Personal and Environment Factors Associated with Attraction to Tropical Urban Parks in Peninsular Malaysia - Mohamad Muslim, Huda Farhana; Yahya, Noor Azlin; Mamat, Mohd Parid (UUM Press, 2018)
There is increasing demand for urban parks as recreational areas amidst urbanization in Malaysia. Urban parks are the most readily accessible resource for interactions with nature across multi groups in many urban cities, including tropical cities. This paper reports a research conducted in 2013/2014 to determine the overall quality of visits and park users level of motivations in selected six public parks in Peninsular Malaysia. The result of this study which examined 2,139 park users in 2013/2014 level of motivation and overall quality of visit in selected six public parks in Peninsular Malaysia and the result shows that about three quarter of the users are youths between 17 and 36 years old. For the quality of visit attributes, park users rated "nature and environment" as the highest dimensions with mean score (M = 4.11). The statistical analysis showed that element of shadiness as an important factor for nature motivation. The common shadiness element experienced by urban park users were considered to be unique landscape and significantly different from Western and developed countries.